Equity in the use of antithrombotic drugs, beta-blockers and statins among Finnish coronary patients - Reunanen Antti; Keskimäki Ilmo; Manderbacka Kristiina; Klaukka Timo (BMC, 2008)
Abstract Background Earlier studies have mainly reported the use of antithrombotic drugs, beta-blockers and statins among hospital patient populations or MI patients. This study aimed to describe the use of these drugs among middle-aged Finnish coronary patients and to identify patient groups in risk of being prescribed inadequate medication for secondary prevention of coronary heart disease. Methods One-year follow-up survey data from a random sample of a cohort of coronary patients were used along with register data linked to the survey. The response rate was 54% (n = 2650). The main outcome measures were use of antithrombotic drugs, beta-blockers and statins and the data were analysed using logistic regression analysis. Results Among men and women, respectively, 82% and 81% used beta-blockers, 95% and 89% used antithrombotic drugs, and 62% and 59% used statins. Younger men and men from higher socioeconomic groups were more likely to use statins, even after controlling for disease severity and comorbidity. In women, the age trend was reversed and no socioeconomic differences were found. Drug use increased with increased disease severity, but diabetes had only a slight effect. Conclusion The use of antithrombotic drugs and beta-blockers among Finnish coronary patients seemed to be rather appropriate and, to some extent, prescription practices of preventive medication varied according to patients' risk of coronary events. However, statin use was remarkably low among men with low socio-economic status, and there is need to improve preventive drug treatment among diabetic coronary patients.